Re-excavation and Interpretation of Key Sections in the Purbeck Group (Tithonian-Berriasian): Teffont Evias, Vale of Wardour, Wiltshire, England - Jonathan D. Radley; Robert A. Coram; Jonathan R. Hall; Margaret Feneley (Geoconservation Research)
The largely non-marine Tithonian-Berriasian (terminal Jurassic–basal Cretaceous) Purbeck Group of the Vale of Wardour, Wiltshire, western England, was well exposed during the nineteenth century and yielded numerous fossils, notably a rich insect fauna from fine-grained micrites of lagoonal origin. In early 2025, re-excavation of the Teffont Evias Lane Cutting and Quarry Site of Special Scientific Interest (around the boundary of the Lulworth and Durlston formations) allowed re-examination of a key part of the succession for its stratigraphy, paleontology and paleoenvironmental interpretation. Current interpretation of the Teffont Evias sections is summarized, with thoughts on future research potential and direction.